An unsteady flow control technique based on negative circulation conception and its application to a blade-divergent passage - Hong, Shuli; Lu, Weiyu; Xiang, Xin; Qiu, Lei (Frontiers in Energy Research, 2023)
A two-dimensional vortex model is introduced in this paper in order to understand the characteristics of the shedding vortex in a blade-divergent passage and to mitigate or suppress it by appropriate methods. The performance of this model under the influence of three typical external factors is studied, namely the main flow extrusion effect, the viscous effect and the transport effect. Based on the analysis, a negative circulation unsteady flow control technique is proposed to compensate for the viscous effect, which we call NCFC. Numerical simulation is performed to verify the effectiveness of the NCFC method. The results show that the NCFC method is superior to the conventional unsteady flow control for improving the performance of the blade-divergent passage in most cases. In additional, there is an optimum injection to suppress the shedding vortex with NCFC which in about 0.2% of the main flow mass and NCFC shows to be more efficient than the conventional flow control in weakening the shedding vortex. Furthermore, NCFC can effectively inhibit separation flow and is shown to be insensitive to the injection flow mass. Finally, the NCFC method is highly recommended to adapt to the situation that the working conditions often change in practice.